Oligometastatic granulosa cell tumor treated with stereotactic body radiation therapy with a radiographic and tumor marker response - Madeline Petty; Vasanti Jhaveri; Nicholas Taylor; Benjamin Foster (Gynecologic Oncology Reports)
Stereotactic body radiation therapy (SBRT) is a safe and effective treatment for oligometastatic gynecologic cancers. This report details the case of a 75-year-old woman with recurrent granulosa cell tumor of the left ovary. The patient was diagnosed with a peritoneal recurrence after her inhibin-B level increased to 39.7 pg/mL, and a subsequent computed tomography (CT) scan of the abdomen and pelvis revealed an enlarging left-sided soft tissue mass in the sigmoid mesentery measuring 1.2 × 1.2 cm. She underwent SBRT, delivering 37.5 Gy in 5 fractions to the soft tissue mass. A CT scan post-treatment indicated the mass had decreased to 0.8 cm and that her inhibin B level decreased to < 7 pg/mL. This case highlights the effectiveness of SBRT in the management of oligometastatic ovarian cancer, achieving a marked radiographic and tumor marker response in patients with disease not amenable to surgical resection.